To assess ovulation in infertile women using urinary luteinizing hormone surge kits versus transvaginal ultrasonography - Karya, Urmila; Chauhan, Vibha; Rani, Anupam (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: The study was conducted to evaluate the efficacy of urinary LH surge kits and TVS to detect ovulation in induced cycles and to compare the ovulation rates by both methods. Methods: Prospective experimental randomized control trial on 72 women with an ovulatory infertility aged 18-35 years, fulfilling the inclusion criteria were given letrozole for ovulation induction. All were randomly divided in two groups. Group 1 woman were asked to check ovulation by urinary LH surge kits and group 2 women were called for follicle monitoring by TVS. Results: Letrozole has no negative effect on endometrium; induced cycle has larger diameter of follicle (median: 22 mm). In induced cycle ovulation occurs later compared to normal cycle (D-16) and half of the women had a BMI more than the recommended WHO criteria (average was 25.28 kg/m2). Number of letrozole cycles (p=0.2642), dose requirement (p=0.0812) and pregnancy rates (10.26% versus 18.19%) were comparable in both groups. Conclusions: TVS is objective, accurate and thus standard modality for ovulation detection. LH surge kit is subjective, having more chances of error but can be used as a good alternative in certain settings like woman of remote area, woman having fear of invasive modality and COVID era woman who are afraid to visit hospital repeatedly.